Odpowiedzi

2010-03-17T15:06:08+01:00
2010-03-17T15:08:06+01:00
A)6(x-4)-2= 6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)½(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x
h)5a(a-3)-3a(a-5)=5a²-15a-3a²+15=2a²-15a+15
2010-03-17T15:09:14+01:00
A)6(x-4)-2
6x-24-2
6x-26
b)2(x+1)-3(x-1)
2x+2-3x+3
-x-1
c)-3(y-2)+4(y+2)
-3y+6+4y+8
y+14
d)5(x-y-1)-4(x+2)
5x-5y-5-4x-8
x-5y-13
e)2(3a+b)-2(a-b)
6a+2b-2a+2b
4a
f)½(4x-4)-2x
2x-2-2x
-2
g)x(x-1)-3(x²-x)
x²-x-3x²+3x
-2x²-2x
h)5a(a-3)-3a(a-5)
5a²-15a-3a²+15a
2a²